Effect of mercury on the total and electrophoretic profile of proteins and on the activity of three enzymes in mantle of three species of freshwater clam : Unio tigridis, Pseudontopsis euphraticus and Anodonta spp: Abd Ali Taker, Sulaf M. Ahmed - Taker, Abd Ali (The Iraqi Journal of Veterinary Medicine, 2008)
A three species of clam Unio tigridis, Pseudontopsis euphraticus andAnodonta sp. were collected from Al-Habaniya lake, Al-Angor region/Iraq.The animals were exposed to three concentrations of mercury :0.1, 0.2 and0.4 mg/L . First group of animals were exposed for three weeks ,secondgroup for two weeks and the third group for one week. At the end of theexposure period, the animals were dissected ,then the mantle removed for thefurther studies on proteins and enzymes. The results were :1- Total protein concentration in the mantle decreased in the threespecies of clam exposed to mercury. It was observed that aprominent effect of mercury on the electrophoretic bands ofproteins with the decrease in the intensity of protein bands orinduction of new bands.2- The activity of the three enzymes : Alkaline phosphatase , ALTand AST were not stable, either increasing or decreasingaccording to the different species and concentration of themercury , for example the activity of alkaline phosphataseincreased in the mantle of the first species at lower anddecreased at the second concentration but decreased in thirdspecies at different concentrations . The activity of ALTincreased in the mantle of the first species at all concentrationsof mercuy, while the activity of AST decreased in the mantle ofthe first species and increased at the two other concentrationsbut decreased in the mantle of third species .3- We concluded from this study that , the clam responses to themercury in the environment, which caused a changes in proteinsand enzymes. These changes can be used as an indicator to thewater pollution with the mercury .